حماية المعلومات والوثائق الإدارية في ظل الأمر 21-09 - ليلى هوام (My University, 2022)
Summary ; In light of Ordinance 09-21, the Algerian legislator addressed information and administrative documents and placed them in different classifications that differ not only according to the importance of the information contained in any administrative document or correspondence, but also from the party of the owner of the document or correspondence according to what is specified in Article 02, and for documents classified in general And it is that which bears the nature of confidentiality. It is forbidden to publish, destroy, photograph or circulate for anyone who is considered to be a public servant, and in order to protect it, legal mechanisms of an administrative nature and others of a penal nature are established, represented in penalties that vary in the degree of the crime committed. ........................ ملخص : تطرق المشرع الجزائري في ظل الأمر 21-09 إلى المعلومات والوثائق الإدارية ووضع لها تصنيفات مختلفة تختلف ليس فقط حسب أهمية المعلومات الموجودة في أي وثيقة إدارية أو مراسلة بل أيضا من جهة صاحبة الوثيقة أو المراسلة وفقا لما هو محدد في المادة 02، وبالنسبة للوثائق المصنفة عموما وهي التي تحمل طابع السرية حظر نشرها أو إتلافها أو تصويرها أو تداولها لكل من يعد في حكم الموظف العام، وفي سبيل حمايتها وضع آليات قانونية ذات طابع إدارية وأخرى ذات طابع جزائي تتمثل في عقوبات تختلف بدرجة الجريمة المرتكبة.
Keywords: key words; Administrative documents; information; confidentiality; secrecy; classified documents; Administrative Mechanisms; Criminal penalties.; الكلمات المفتاحية : الوثائق الإدارية، المعلومات، السرية، الوثائق المصنفة، الآليات الإدارية، العقوبات الجزائية .